Corpo e cidade: comunicação e contaminação - Costa, Pablo Assumpção Barros (2006)
The research investigates the connection between the body and the city as a systemic structural coupling through which the flux of informatio n is organized as communicative process. In order to do so, we analyze the concept of environment according to a few bio -semiotic theories (Uexküll, 2004), the concept of embodiment assessed by the bodymedia theory (Katz and Greiner, 2005), the concepts of sign and semiosis according to C. S. Peirce s commentators (Nöth 1990, Queiroz 2004), and a few important questions raised regarding representation in art and theory. The study of the relationship between body and space as communicative process provides evidence of the ambivalence involved in the live organization of information and knowledge. As the result of the research, we provide the theoretical discussion plus two performative writing exercises and three art works in digital video about two cities that were objects of our study: Fortaleza and São Paulo. The art works combine theoretical references, memory, personal confession and fiction